Honeybush extract as a viable intervention against oxidative stress and mitochondrial dysfunction in a glucotoxic in vitro model - Le Roux, Kyle (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2024.